Psycho-Didactic Dimensions of Various Opening and Closing Surahs of the Al-Qurán and Their Implementation in PAI Learning in Madrasas - Solehudin, Deni; Mahmud, Mahmud; Hafid, Hafid; Sarbini, Sarbini (Hanifiya: Jurnal Studi Agama-Agama, 2024)
Education is a complex and dynamic process that aims to shape individuals with character and broad knowledge. In the educational process, teachers play a central role in guiding and leading students to achieve learning objectives. One of the important aspects of learning is the teacher's skill in opening and closing lessons. This skill is very important to attract students' attention, motivate them to learn, and help them understand the lesson material better. The Quran, as a guide for Muslims, has values that can be applied in various aspects of life, including in the field of education. Various openings and closings of Quranic surah contain psycho-didactic dimensions that can be applied to improve the quality of learning. This study aims to examine the psycho-didactic dimensions in various openings and closings of Quranic surah and their implementation in opening and closing lesson skills. This study uses qualitative and quantitative methods. Qualitative methods are used to find classifications of various openings and closings of Quranic surah and to analyze the psycho-didactic dimensions in various openings and closings of Quranic surah, while quantitative methods are used to analyze the implementation of psycho-didactic dimensions in opening and closing lesson skills. Data were collected through questionnaires, observations, interviews, and documentation. The results of the study show that various openings and closings of the Quranic surah contain psycho-didactic dimensions, especially affective and psychomotor dimensions. The implementation of psycho-didactic dimensions in opening and closing lesson skills shows positive results. Students are more motivated and enthusiastic in participating in learning and have a better understanding of the lesson material. The psycho-didactic dimensions in various openings and closings of Quranic surah can be applied to improve the quality of learning. The implementation of psycho-didactic dimensions in opening and closing lesson skills has proven to be effective in increasing interest, motivation, and enthusiasm.